Prática docente : dificuldades, possibilidades e transformações das práticas no ensino de webjornalismo - Teixeira, Douglas de Araujo (2013)
Journalism have undergone, due to the emergence and popularization of Internet, meaningful changes in its process of production and dissemination of content, higher education courses that prepare professionals for this area - supported by the Ministry of Education Curriculum Guidelines - seek to integrate subjects into their curriculum that aim at producing news content for the internet. In that context, considering the key role of a college education professor in training qualified professionals, this research investigated the educational practice of Journalism professors at a private university in Santos, in order to get familiar with the teaching practice in journalistic production to the internet, as well as the impacts that technology caused to that practice, specifically the use of a platform for content publishing. Based on studies of Bahia (2009), Canavilhas (2001), Ferrari (2010), Mielnickzuc (2003), Moherdaui (2007), Rossi (2007), among others, the study had the purpose of contextualizing the current way of doing journalism; regarding the practice of teaching, it was supported by studies of Corrêa et al. (2011) and Franco (2011), and to discuss the reflective teacher, the work found basis on the work of Pimenta (2006) and Schön (2000). The work of Primo (2010), provided input for the discussion of a scenario of digital journalism teaching in Brazil. The research approach was qualitative and used as a tool to collect data to observe the lessons of professors responsible for the subject of journalistic production for the internet, which also participated in the recordings and interviews. The observation made to the practice of teaching was also carried out with the use of autoscopy technique, which consists of the recording and subsequent analysis of the image by the recorded individual. The results indicated that the use of technology allowed students greater autonomy in the production and publication of materials. For the professor, more appropriate practices were made it possible to their context of work, and the autoscopy sessions awakened in them the need for further changes to the practice.